2013
DOI: 10.1093/gerona/glt177
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Aging Exacerbates Blood-Brain Barrier Disruption, Neuroinflammation, and Oxidative Stress in the Mouse Hippocampus: Effects on Expression of Genes Involved in Beta-Amyloid Generation and Alzheimer's Disease

Abstract: There is growing evidence that obesity has deleterious effects on the brain and cognitive function in the elderly population. However, the specific mechanisms through which aging and obesity interact to promote cognitive decline remain unclear. To test the hypothesis that aging exacerbates obesity-induced cerebromicrovascular damage and neuroinflammation, we compared young (7 months) and aged (24 months) high fat diet-fed obese C57BL/6 mice. Aging exacerbated obesity-induced systemic inflammation and blood-bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
242
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(258 citation statements)
references
References 63 publications
15
242
0
1
Order By: Relevance
“…On the one hand, 4 months of western diet given to 3 and 12 months APPswe/PS1 mice did not compromise BBB integrity (Theriault, ElAli, & Rivest, 2016). However, in another study, HFD‐induced obesity was shown to exacerbate BBB permeability in aged mice (24 months) measured by IgG extravagated to the hippocampus (Tucsek et al, 2014). The percentage of saturated fat in the diet of the latter study was the same as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, 4 months of western diet given to 3 and 12 months APPswe/PS1 mice did not compromise BBB integrity (Theriault, ElAli, & Rivest, 2016). However, in another study, HFD‐induced obesity was shown to exacerbate BBB permeability in aged mice (24 months) measured by IgG extravagated to the hippocampus (Tucsek et al, 2014). The percentage of saturated fat in the diet of the latter study was the same as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In others, obesity exacerbated early postischemic BBB disruption in 16‐week‐old mice fed HFD. Tucsek et al (2014) showed that 7 months of HFD did not change the BBB permeability (measured by IgG levels) in the hippocampus, but an exacerbated damage of the BBB was found at 24 months with HFD. The impact of HFD on memory and cognition is also controversial and depends on the composition of the fat and the time of exposure to HFD.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescent labeling for CD31 was used to identify microvessels in the brain as we previously described (Toth et al 2013a;Tucsek et al 2014;Warrington et al 2011). Capillary density in the CA1 region of the hippocampus was quantified, using stereological methods, as the length of blood vessels <10 μm in diameter per volume of tissue using Neurolucida with AutoNeuron (MicroBrightField, Williston, VT).…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…Targeted qPCRarray to analyze mRNA expression of pro-and anti-angiogenic factors A quantitative real time RT-PCR technique was used to analyze mRNA expression of genes known to be involved in regulation of angiogenesis and microvascular regression in hippocampi of mice from each experimental group as reported (Toth et al 2013a;Tucsek et al 2003;Tucsek et al 2014;Csiszar et al 2013). In brief, total RNA was isolated with a Mini RNA Isolation Kit (Zymo Research, Orange, CA) and was reverse transcribed using Superscript III RT (Invitrogen) as described previously (Bailey-Downs et al 2012a).…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
See 1 more Smart Citation